A field-based Conservation Welfare Assessment Framework for Costa Rican primate sanctuaries - Siobhan I.M. Speiran (Human-Animal Interactions)
Abstract This article offers a methodological contribution to the study of field-based wild animal welfare assessments in developing tourism contexts. Grounded in the interdisciplinary fields of conservation welfare and ethnoprimatology, it introduces a preliminary, non-invasive, transdisciplinary, and field-based Conservation Welfare Assessment Framework (CWAF) tailored to non-human primate sanctuary attractions in Costa Rica. This holistic approach provides 24 evaluative criteria across eight categories: mental experiences, good environment, physical health, tourism events, conservation projects, community outreach, and environmental education. Emphasizing a relational and accessible methodology similar to multispecies ethnography, the framework encourages mixed, socio-ecological methods including participant observation, behavioural observation, document review, and social inquiry with key informants, community members, and tourists to guide data collection. Finally, I reviewed framework’s applications with suggestions for future research.